2020
DOI: 10.1016/j.cegh.2019.04.011
|View full text |Cite
|
Sign up to set email alerts
|

Risk behaviours related to hepatitis B virus infection among adults in Malaysia: A cross-sectional household survey

Abstract: Background: The objective of this study was to identify the magnitude of various risk behaviours related to Hepatitis B (HepB) and to characterize the relationship between socio-demographic determinants and these risk factors among adults in Malaysia. Methods: We conducted a cross-sectional study in nine districts in the state of Selangor in 2016. A two-stage cluster sampling design was used and adults aged 20 years or above who were living in the selected living quarters were interviewed face-to-face. A multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 65 publications
(133 reference statements)
0
2
0
Order By: Relevance
“…The latter is consistent with other people's reports [19,47,[83][84][85]. Each study design makes a significant contribu-tion to the overall prevalence while also providing unique viewpoints on the connection between HBV and HCC in the Southeast Asian context [86,87].…”
Section: Discussionsupporting
confidence: 87%
“…The latter is consistent with other people's reports [19,47,[83][84][85]. Each study design makes a significant contribu-tion to the overall prevalence while also providing unique viewpoints on the connection between HBV and HCC in the Southeast Asian context [86,87].…”
Section: Discussionsupporting
confidence: 87%
“…Previous studies also reported that HBsAg positivity was more prevalent among the Chinese than other ethnic group in Malaysia 6 , 13 . Although the reasons behind the high rate of HB in certain ethnic groups are still unknown, previous study suggested that high-risk behaviour and cultural activity, such as unhygienic tattooing, body piercing, high-risk sexual activities, and alcohol consumption may have been contributed to high prevalence of HBsAg and Anti-HBc 22 , 29 . Thus, further study on the association of lifestyles, behaviour or occupational risk exposures and HBV infection in different populations and ethnicities were needed in order to explain the different levels of HB infection between different populations.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, those who used smoking, alcohol drinking and low HBV knowledge will have an increased chance to expose the risk of HBV similar findings were reported from Ataei et al 9 and Frew et al 17 . On the other hand, those who don't smoke or drink alcohol and have a high knowledge will have a decreased chance to expose the risk of HBV 18,19 .…”
Section: Ofmentioning
confidence: 99%